The Effect Of Personality And Competence On The Performance Of Lecturers In The Management Study Program At Lamappapoleonro University - Asmini Asmini; Andi Muhammad Yusuf (GENTARA: management and accounting research, 2025)
This study explores the influence of personality and competence on the performance of lecturers in the Management Study Program at Universitas Lamappapoleonro. In the context of higher education, lecturers' professional growth is influenced by various factors, including their personal traits and professional competencies. The research aims to assess how these factors affect their ability to carry out the Tri Dharma of Higher Education, which includes teaching, research, and community service. The study employs a causal-explanatory research design to test the hypothesis that personality traits and competencies significantly impact the performance of lecturers in the Management program. Data was collected using structured surveys, and the analysis reveals that both personality and competence play critical roles in enhancing lecturers' job performance. The findings suggest that improving lecturers' personal development and professional skills can lead to better performance outcomes, benefiting both individual lecturers and the university's broader goals. This research contributes to the understanding of how personal and professional growth impact academic performance and provides practical recommendations for policy makers in higher education institutions to foster a supportive environment for lecturer development